Towards Open Innovation in Health Care - Bullinger-Hoffmann, Angelika; Möslein, Kathrin; Raß, Matthias (Proceedings of the European Conference on Information Systems (ECIS), 2012)
Many countries face severe challenges in health care, especially soaring costs. Innovative products and services are needed to help increase the quality of care and to reduce costs. In the field of rare diseases, which often is not attractive economically, the situation is even more serious. Building on extant research on open innovation, we use a design science approach to study an open innovation platform for rare diseases. Like many other open innovation practices, e.g. innovation communities and innovation contests, the platform is based on modern information and communication technologies, and is designed to be accessible from anywhere and anytime, thus supporting asynchronous interaction between the locally dispersed participants. Analysis of participation details, submitted innovative concepts, and content of communication shows acceptance by patients and other relevant stakeholders, e.g. family members, caregivers, and health care professionals. Activity on the platform, i.e. almost 200 innovative submissions, 800 comments, and more than 1,800 personal messages, is found to be helpful for collaborative innovation and emotionally supportive for participants. Generalizing from the special field of rare diseases, implications concerning the suitability of open innovation approaches in health care from a theoretical, methodological, and management perspective close the paper.
WiSo-Import:2015-04-17:4275
Keywords: Open innovation; Health care; Design science